Predictors of mortality in individuals infected with dengue: An Indian case study - Parthraj Shenoy; Ashok Kumar Pannu; Atul Saroch; Sourabh S. Sharda; Mandeep Bhatia; Deba Parsad Dhibar (Medicina Clínica Práctica)
Background and objectives: Dengue infection and its associated complication contributes to a significant number of deaths as per World Health Organization (WHO) statistics. The aim of the study is to identify Predictors associated with mortality in Dengue infection. Materials and methods: In this prospective observational study conducted at the tertiary care hospitals of north India from August 2023 to December 2024, confirmed cases of dengue fever with a duration of less than seven days were recruited. Patients classified into Survivors or non-survivors, variables that were found to have statistically significant associations on univariate analysis were subjected to multivariate analysis by logistic regression by enter method for predictors of dengue mortality. Results: A total of 158 dengue patients were recruited of which 18 (11.4%) died from the disease. Altered mental status, dyspnea at rest, and decreased urine output were significantly more frequent among non-survivors. Regarding laboratory parameters, non-survivor group exhibited significantly elevated levels of total leukocyte count, urea, creatinine, liver enzymes and International normalized ratio. Application of logistic regression using 3 factors-qSOFA (quick sequential organ failure assessment), creatinine and ferritin were performed which showed a statistically significant association with creatinine and ferritin. Odd Ratio (OR) for creatinine 1.449 indicates that for every unit increase in creatinine, the odds of mortality increase by 44.9%. Although the OR is exactly 1, the tight CI around 1 suggests that elevated ferritin is associated with mortality, but with a small effect size (p – 0.047). Conclusions: The presence of raised creatinine and elevated serum ferritin were predictors associated with a higher risk of mortality. Resumen: Antecedentes y objetivos: La infección por dengue y sus complicaciones asociadas contribuyen a un número significativo de muertes, según las estadísticas de la Organización Mundial de la Salud (OMS). El objetivo del estudio es identificar los predictores asociados con la mortalidad en la infección por dengue. Materiales y métodos: En este estudio observacional prospectivo, realizado en hospitales de atención terciaria del norte de la India entre agosto de 2023 y diciembre de 2024, se reclutaron casos confirmados de dengue con una duración inferior a siete días. Los pacientes, clasificados como sobrevivientes y no sobrevivientes, se sometieron a un análisis multivariante mediante regresión logística por el método de entrada para los predictores de mortalidad por dengue. Resultados: Se reclutaron 158 pacientes con dengue, de los cuales 18 (11,4%) fallecieron a causa de la enfermedad. La alteración del estado mental, la disnea en reposo y la disminución de la diuresis fueron significativamente más frecuentes entre los no supervivientes. En cuanto a los parámetros de laboratorio, el grupo de no supervivientes presentó niveles significativamente elevados de recuento total de leucocitos, urea, creatinina, enzimas hepáticas y razón internacional normalizada (IRN). Se realizó una regresión logística con 3 factores: qSOFA (evaluación secuencial rápida de fallo orgánico), creatinina y ferritina, que mostró una asociación estadísticamente significativa. Un OR (odd ratio) para la creatinina de 1449 indica que por cada unidad de aumento de creatinina, la probabilidad de mortalidad aumenta un 44,9%. Aunque el OR es exactamente 1, el IC estrecho en torno a 1 sugiere que la ferritina elevada se asocia con la mortalidad, pero con un tamaño del efecto pequeño (p – 0,047). Conclusiones: La presencia de niveles elevados de creatinina y ferritina sérica fueron predictores asociados con un mayor riesgo de mortalidad.